Reading The Fringes: Applying A Social-Semiotic Frameworkto Analyse Students' Drawings of Two-Source LightInterference - Zahra Intan Nandita; Irma Fitria Amalia (IPI Garut Press, 2026)
This study applies the social-semiotic analytical framework developed by Tang et al. (2019) to examine how senior high school students visually represent the concept of two-source light interference in their self-generated drawings. Interference is a canonical topic in physical optics: light from two coherent sources combines constructively or destructively depending on path difference, producing the alternating bright and dark fringes first documented by Young (1800). Because the phenomenon is inherently spatial and wave-like, it poses a distinctive representational challenge for learners, who must depict two overlapping wave sources, a path difference, and a resulting fringe pattern all at once. Using a Predict-Observe-Explain task, 33 eleventh-grade students produced diagrams of a two-slit interference demonstration before and after instruction. Drawings were coded using five categories. Framework: association, spatial, movement, perspective, and textual contextualization. Findings show that most students' initial drawings depicted the light sources and screen but omitted the path-difference relationship that causally explains the fringe pattern, a gap that closed substantially, though not completely, after instruction. The paper discusses implications for using drawing-based formative assessment in physics instruction on wave phenomena.